(untitled) (Pedagogy of Higher and Secondary Education, 2000)
This article describes the inculcation o f diagnostic technologies into teaching process o f higher school. The author gives the definition o f diagnostic technologies, function, the object оf diagnostic methods. The article deals with the main principles of diagnostic process, methods of using diagnostic technologies , luring the lessons on pedagogical discipline.